Assessment of anti-oxidant activity and High-Performance Thin-Layer Chromatography characters of different compositions of Triphala powder: Silva H.H.S.S., Hapuarachchi S.D.*, Madhushika K.D.C., Perera P.K. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Triphala: a polyherbal formulation used in both Ayurveda and Sri Lankan Traditional Medical practices. Aim of the present study is to compare the chemical characteristics of distinct compositions of Triphala powder as mentioned in various Ayurveda Authentic Texts. Dried fruits of Terminalia chebula Retz. (TC), Terminalia bellirica Gaertn. (TB), and Phyllanthes emblica (PE) were purchased and authenticated. Followed by a comprehensive literature review, five different compositions of Triphala dried powdered samples as S1 (1:1:1), S2 (1:2:3), S3 (1:2:4), S4 (1:2:2) TC: TB: PE respectively and S5 – 1:2:4 ratio based on the fruits of TC: TB: PE were subjected to ethanol extractions. Anti-oxidant activity and High-Performance ThinLayer Chromatography (HPTLC) characters of the five samples was evaluated. HPTLC analysis of the samples against the standard solutions of Gallic acid (GA) and Tannic acid (TA) was carried out with Toluene: Ethyl acetate: Formic acid (2:5:1.5) as the mobile phase. Antioxidant activity was evaluated using 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) assay against the standard Ascorbic Acid (AA). The HPTLC analysis of all five samples showed similar patterns with respect to their peaks and intensities while showing peaks corresponding to the peaks of standards. A high level of anti-oxidant activity was found in the samples varying in the decreasing order of S3 (1:2:4) > S1 (1:1:1) > S4 (1:2:2 )> S2 (1:2:3) > S5 (1:2:4 Fruits). In spite of the high level of antioxidant activity observed with all five samples, the most pronounced level of antioxidant activity was found in S3 powder sample. Further studies need to be carried out on bioactivity studies to evaluate the therapeutic efficacy of different compositions of Triphala powder. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">